2014
DOI: 10.1007/s10433-014-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Are physically frail older persons more at risk of adverse outcomes if they also suffer from cognitive, social, and psychological frailty?

Abstract: Frailty is considered a predictor for negative outcomes such as disability, decreased quality of life, and hospital admission. Frailty measures have been developed that include different dimensions. We examined whether people who are physically frail are more at risk for negative outcomes of frailty if they also suffer from psychological, cognitive, or social frailty. Frailty was measured at baseline by means of the Groningen Frailty Indicator (GFI), which comprises a physical, cognitive, social, and psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 35 publications
5
48
0
Order By: Relevance
“…27 Another study reported that physical frailty could predict the incidence of disability; however, the cognitive and social domains had no additional effects on disability among older people who already suffered from physical frailty. 28 The present results are in agreement with these previous studies, and highlighted the impact of physical status on the incidence of disability using statistical modeling.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…27 Another study reported that physical frailty could predict the incidence of disability; however, the cognitive and social domains had no additional effects on disability among older people who already suffered from physical frailty. 28 The present results are in agreement with these previous studies, and highlighted the impact of physical status on the incidence of disability using statistical modeling.…”
Section: Discussionsupporting
confidence: 93%
“…One of the few studies that have compared the effects of the health deficit between the three domains (physical, cognitive and social) of health status on the onset of disability showed that physical frailty was mostly responsible for the predictive validity of adverse health outcomes, including disability . Another study reported that physical frailty could predict the incidence of disability; however, the cognitive and social domains had no additional effects on disability among older people who already suffered from physical frailty . The present results are in agreement with these previous studies, and highlighted the impact of physical status on the incidence of disability using statistical modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical frailty predicts incident cognitive impairment (Canevelli et al, 2015). However, previous research yielded mixed results as to whether cognitive impairment had additional impact on disability for those who are already physically frail (Ament et al, 2014;Avila-Funes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“… 87 Similarly, a Dutch study showed that almost half of frail participants still report a good to excellent quality of life. 88 …”
Section: Introductionmentioning
confidence: 99%